Relative Age Effect: A Systematic Discrimination against Biologically Younger Athletes - Gioldasis, A.; Bekris, E.; Smirniotou, A. (Central European Journal of Sport Sciences and Medicine, 2021)
Physical differences associated with birth-date among athletes of the same selection year have been described as the Relative Age Effect (RAE). The aim of this study was to examine whether RAE still exists in soccer and running sport disciplines as well as to evaluate its progress among different gender, age, and sport context and if it has an effect on performance. Using official archives of the international sports` associations (World Athletics-UEFA), birthdates and performance were collected for 7226 athletes (4033 males; 3198 females) who participated in soccer and running events. A chi-square test was used to assess differences between observed and expected birth date distributions. The study showed an over-representation of athletes born in the first quarter of the selection year for both soccer and running events. RAE is more obvious in younger age groups and in sports that require higher explosive speed, strength, power and anaerobic capacity such as soccer and short distance sprints. It was also found that RAE is associated with performance. In conclusion, athletes of younger age groups with greater biological age have a physical advantage in explosive sports (i.e. soccer and short distance running) that probably does not predict their future development.